Possible Roles of Proinflammatory and Chemoattractive Cytokines Produced by Human Fetal Membrane Cells in the Pathology of Adverse Pregnancy Outcomes Associated with Influenza Virus Infection - Noboru Uchide; Kunio Ohyama; Toshio Bessho; Makoto Takeichi; Hiroo Toyoda (Mediators of Inflammation)
Pregnant women are at an increased risk of influenza-associated adverse outcomes, such as premature delivery, based on data from the latest pandemic with a novel influenza A (H1N1) virus in 2009-2010. It has been suggested that the transplacental transmission of influenza viruses is rarely detected in humans. A series of our study has demonstrated that influenza virus infection induced apoptosis in primary cultured human fetal membrane chorion cells, from which a factor with monocyte differentiation-inducing (MDI) activity was secreted. Proinflammatory cytokines, such as interleukin (IL)-6, tumor necrosis factor (TNF)-α, and interferon (IFN)-β, were identified as a member of the MDI factor. Influenza virus infection induced the mRNA expression of not only the proinflammatory cytokines but also chemoattractive cytokines, such as monocyte chemoattractant protein (MCP)-1, regulated on activation, normal T-cell expressed and secreted (RANTES), macrophage inflammatory protein (MIP)-1β, IL-8, growth-regulated oncogene (GRO)-α, GRO-β, epithelial cell-derived neutrophil-activating protein (ENA)-78, and interferon inducible protein (IP)-10 in cultured chorion cells. These cytokines are postulated to associate with human parturition. This paper, therefore, reviews (1) lessons from pandemic H1N1 2009 in pregnancy, (2) production of proinflammatory and chemoattractive cytokines by human fetal membranes and their functions in gestational tissues, and (3) possible roles of cytokines produced by human fetal membranes in the pathology of adverse pregnancy outcomes associated with influenza virus infection.